The strategy and consistency of Federal Reserve monetary policy, 1924-1933 - Wheelock, David C. (Cambridge [England] ; New York : Cambridge University Press, 1991)
A study of the impact of monetary policy in the United States on the causes of the Great Depression.
Includes bibliographical references (p. 120-123) and index.
oif 23/02/15
Loan
Keywords: Board of Governors of the Federal Reserve System (U.S.); Federal Reserve banks; Monetary policy -- United States -- History -- 20th century